Bridging modelling and policymaking efforts to realize the European bioeconomy. Issue 11 (12th September 2022) - Christensen, Thomas; Philippidis, George; van Leeuwen, Myrna; Singh, Asha; Panoutsou, Calliope
Abstract: The European Bioeconomy Strategy aims to facilitate the transition from a take–make–dispose fossil economy into one fostering circular bio‐based value chains linking sustainable land use with cutting‐edge products. Optimized designs, implementation and monitoring rely on continuous interactions between policymakers and modellers who run multiple scenarios for environmentally, economically and socially desirable futures. This paper leverages a multi‐layered framework that cross‐references 39 policies and 32 models to assess how they address the five principle objectives of the Bioeconomy Strategy in terms of accompanying sectors, value chains and multi‐dimensional indicators. The framework identifies gaps in bioeconomy knowledge both in policy and modelling. Overall, the analysis found little mention of the wide range of bio‐based products, technologies and processes, bio‐refineries, waste and land conservation. Bio‐based product policies can be simulated only in a limited number of models, compared, for example, to the wide range of modelling capacities that can model bioenergy. Additionally, in both policy and modelling realms, integration of market and biophysical drivers within the full scope of the value chain is scarce. Multidisciplinary studies combining multiple models perform best in this respect by integrating a more comprehensive range of relevant policies, bioeconomy drivers and indicators. Findings point to a more significant issue in policy‐modelling information exchange, and this paper discusses the challenges and opportunities for future improvements in this collaboration. Abstract : Policymakers and modellers continuously interact to produce scenarios for environmentally, economically and socially desirable futures. This paper cross‐references 39 policies and 32 models to assess how they address the five objectives of the Bioeconomy Strategy in terms of accompanying sectors, value chains and multi‐dimensional indicators. Principle gaps observed are the limited policy mechanisms or modelling frameworks available covering the market uptake and sustainability of bio‐based products and processes. These equally fail to integrate ecosystem with economic indicators. Key studies found are those combining multiple models. Model‐policy collaboration challenges include access to high‐level cross‐government reports, data availability and coordination, and interdisciplinary modelling.